Intercalation of flufenamic acid into magnesiumaluminum-layered double hydroxide and zincaluminum-layered double hydroxide for the formation of controlled release drugs / Monica Limau Jadam - Jadam, Monica Limau (2018)
ABSTRACT Flufenamic acid, a non-steroidal anti-inflammatory drug (NSAID) was successfully intercalated into Magnesium-Aluminum-layered double hydroxide (Mg/Al-LDH) and Zn-Al-layered double hydroxide (Zn/Al-LDH) by self-assembly method at concentration of 0.6 M flufenamic acid and molar ratio of Mg/Zn:Al = 2. The nanocomposites were synthesized until reached their optimum pH to enhance the intercalation process. The optimum pH for Magnesium-Aluminum-flufenamic acid (Mg/Al-FA) is at pH10 and Zn-Al-flufenamic acid (Zn/Al-FA) is at pH7.5. Upon the successful intercalation of the drug, release profiles and the factors govern its release from their matrices into various aqueous media were determined. The relatively phase-pure with well-ordered layered nanohybrid materials were successfully synthesized by self-assembly method at optimum condition. Expansion of basal spacing was observed from 9.8 A in the Mg/Al-LDH to 23.5 A in the Mg/Al-FA-LDH and 8.9 A in the Zn/Al-LDH to 21.0 A in the Zn/Al-FA-LDH nanocomposite obtained from the analysis by using PXRD. The results were supported by the data obtained from the whole analysis using FTIR, TGA/DTG, UV-Vis, CHNS, ASAP and ICPAES. Controlled release study of the drug into the aqueous solutions of sodium carbonate solution, sodium chloride solution and saline solution were performed. The release of drug into the aqueous media is in the order of; sodium carbonate > sodium chloride > saline solution with the percentage release of 50%, 30% and 20% for Mg/Al-FA-LDH and 53%, 42% and 20% for Zn/Al-FA-LDH, respectively. The release profiles are best described by pseudo-second order kinetic model as shown by the regression values of about 1.0. The FA anion was successfully intercalated into Mg/Al-LDH and Zn/Al-LDH with the percentage loading of guest anions which are 63.37% and 63.40%, respectively. This study shows that the Mg/Al-LDH and Zn/AlLDH can be used as a matrix for controlled release formulation of FA drug. The release of FA from the matrix was found to be controlled by the anion in the release aqueous solution as well as the type of the release media.